Characterization of polymer nanowires fabricated using the nanoimprint method - Viphavakit, Charusluk; Atthi, Nithi; Boonruang, Sakoolkan; Themistos, Christos; Mohammed, Waleed Soliman; Kalli, Kyriacos; Rahman, Bilkish M Azizur; Komodromos, Michael (My University, 2014)
In this paper, an ormocomp polymer nanowire with possible use in integrated-optics sensing applications is presented. We discuss the structure design, the fabrication process and present results of the simulation and characterization of the optical field profile. Since the nanowires are designed and intended to be used as integrated optics devices, they are attached to tapered and feed waveguides at their ends. The fabrication process in this work is based mainly on the nanoimprint technique. The method assumes a silicon nanowire as an original pattern, and polydimethylsiloxane (PDMS) as thesoft mold. The PDMS mold is directly imprinted on the ormocomp layer and then cured by UV light to form the polymer based nanowire. The ormocomp nanowires are fabricated to have various dimensions of width and length at a fixed 500nm thickness. The length of the nanowires is varied from 250 μm to 2 mm, whereas the width of the structures is varied between 500nm and 1μm. The possible optical mode field profile that occurs in the proposed polymer nanowire design is studied using the H-field finite element method (FEM). In the characterization part, the optical field profile and the intensity at the device output are the main focus of this paper. The various lengths of the nanowires show different characteristics in term of output intensity. An image processing is used to process the image to obtain the intensity of the output signal. A comparison of the optical field and output intensity for each polymer nanowire is also discussed.
Keywords: Integrated optics; Nanoimprint; Polymer nanowires